Description of a new species of Toumeyella Cockerell (Hemiptera, Coccidae) from Mexico, with a taxonomic key to mexican species - Takumasa Kondo (Revista Brasileira de Entomologia, 2011)
A new species of soft scale insect from Mexico, Toumeyella fontanai Kondo & Pellizzari sp. nov. is des-cribed and illustrated. A taxonomic key to the species of scale insects of the genus Toumeyella Cockerell known in Mexico is provided.